IMPLEMENTING EFFECTIVE PROMOTION OF HEALTHY LIFESTYLE AMONG THE YOUNG GENERATION OF ADOLESCENTS (European Journal of Interdisciplinary Research and Development, 2025)
Modern society faces numerous challenges related to the physical and mental health of adolescents. One of the most important factors influencing the formation of a healthy lifestyle is its effective promotion among young people. This article discusses strategies and methods aimed at introducing a healthy lifestyle culture among adolescents. The focus is on the need for an integrated approach to promoting healthy eating, physical activity, preventing bad habits and developing emotional intelligence. International programs and national initiatives in this area are also reviewed, and prospects for further research and improvement are discussed.